The Interlanguage Rhythm of Algerian EFL Undergraduates - ALOUACHE, Amel (Journal of Human Sciences, 2016)
This paper is an attempt to classify the rhythm of the interlanguage produced by third year Algerian EFL students at Constantine 1 University. The nature of speech rhythm classes has been hotly debated as to whether it should be conceived as a discrete stress-timed vs. syllable-timed dichotomy or as a continuum. The rhythm metrics measured in this study i.e. %V and ∆C, yield that the informants’ speech rhythm is rather ‘intermediate’, merging a stress-timed ∆C and a syllable-timed %V. Accordingly, the results obtained support those who believe that crosslinguistic interference in the area of phonology touches not only segments but also speech rhythm.